2018
DOI: 10.1038/s41416-018-0328-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in clinical cancer immunotherapy

Abstract: Cytokines are soluble proteins that mediate cell-to-cell communication. Based on the discovery of the potent anti-tumour activities of several pro-inflammatory cytokines in animal models, clinical research led to the approval of recombinant interferon-alpha and interleukin-2 for the treatment of several malignancies, even if efficacy was only modest. These early milestones in immunotherapy have been followed by the recent addition to clinical practice of antibodies that inhibit immune checkpoints, as well as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
658
1
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 907 publications
(672 citation statements)
references
References 116 publications
2
658
1
11
Order By: Relevance
“…In terms of the ability of the immune system to detect and eliminate malignant cancer cells, various cytokines have been investigated for potential prognosis markers and treatment options in cancers (Lee & Margolin, 2011; Nicholas & Lesinski, 2011). In this regard, it has been shown that several cytokines can restrict tumor growth by stimulating immune effector cells, direct antiproliferative or proapoptotic activity against tumors (Berraondo et al, 2019). It has been recognized that a number of cytokines including interleukins (IL‐2, IL‐7, IL‐12, IL‐15, IL‐18, and IL‐21), growth factors (GM‐CSF), and interferons (IFN‐α) have efficacy in clinical studies for patients with advanced cancers (Waldmann, 2018).…”
Section: The Role Of Cytokines In Cancer Immunotherapymentioning
confidence: 99%
“…In terms of the ability of the immune system to detect and eliminate malignant cancer cells, various cytokines have been investigated for potential prognosis markers and treatment options in cancers (Lee & Margolin, 2011; Nicholas & Lesinski, 2011). In this regard, it has been shown that several cytokines can restrict tumor growth by stimulating immune effector cells, direct antiproliferative or proapoptotic activity against tumors (Berraondo et al, 2019). It has been recognized that a number of cytokines including interleukins (IL‐2, IL‐7, IL‐12, IL‐15, IL‐18, and IL‐21), growth factors (GM‐CSF), and interferons (IFN‐α) have efficacy in clinical studies for patients with advanced cancers (Waldmann, 2018).…”
Section: The Role Of Cytokines In Cancer Immunotherapymentioning
confidence: 99%
“…The addition of cancer vaccines (with either peptide vaccines or with primed dendritic cell vaccines) or the additional of radiation therapy to increase neoantigen formation and recognition may augment T cell responses and tumor recognition [35,[239][240][241][242] . Similarly, adding cytokines that stimulate the immune system such as IFN-a, IL-2, IL-12, IL-10 and the granulocyte-macrophage colony-stimulating factor (GM-CSF) to the treatment regimen or at high concentrations directly into the tumor microenvironment may also alter immune responses [243] .…”
Section: Novel Therapies To Bypass Resistancementioning
confidence: 99%
“…Immunostimulatory recombinant cytokines promote lymphocyte activation via control of transcriptional and metabolic programmes [35]. An example is recombinant IL-2 (aldesleukin, Proleukin ® ) that has been used to treat renal cancer and melanoma [36].…”
Section: Recombinant Cytokinesmentioning
confidence: 99%